2015
DOI: 10.1039/c5ta00890e
|View full text |Cite
|
Sign up to set email alerts
|

Porous carbon-coated CuCo2O4 concave polyhedrons derived from metal–organic frameworks as anodes for lithium-ion batteries

Abstract: A MOF is employed as a template and carbon resource for the synthesis of porous carbon-coated CuCo2O4 concave polyhedra, exhibiting an excellent capacity and cycling reversibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(46 citation statements)
references
References 50 publications
1
40
0
5
Order By: Relevance
“…S5) 3, 4, 48 . Moreover, the high irreversible capacity loss can also be attributed to the volume variations, some undecomposed Li 2 O phase, along with the irreversible reduction of active materials and electrolyte during the first discharge process 11, 6466 . Notably, the curves are strongly overlapped for 25, 50 and 100 cycles, suggesting the good stability and reversibility of CuFeO 2 @rGO electrode.
Figure 4( a ) CV curves of CuFeO 2 @rGO.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5) 3, 4, 48 . Moreover, the high irreversible capacity loss can also be attributed to the volume variations, some undecomposed Li 2 O phase, along with the irreversible reduction of active materials and electrolyte during the first discharge process 11, 6466 . Notably, the curves are strongly overlapped for 25, 50 and 100 cycles, suggesting the good stability and reversibility of CuFeO 2 @rGO electrode.
Figure 4( a ) CV curves of CuFeO 2 @rGO.
…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, searching for new anode materials with ultrahigh theoretical capacity and remarkable electrochemical performance is urgently required 8, 9 , due to the low theoretical capacity for the current commercial graphite anodes 10 . Considerable researches have been devoted to the design of transition metal oxides (TMOs) based electrodes including the binary, ternary, and complex metal oxides, for application in high-performance energy storage devices 1118 . Among TMOs, the ternary oxides with delafossite structure (ABO 2 ) and spinel structure (AB 2 O 4 ) have unique layered crystal structures with three-dimensional diffusion pathways, which are benefit for lithium ion insertion and extraction 1923 .…”
Section: Introductionmentioning
confidence: 99%
“…[71] Zhang et al reported a way to directly grow ZnO@ZnO quantum dots/C core-shell nanorod arrays (NRAs) on a flexible carbon cloth substrate based on a facile and scalable in situ ion exchange process (Figure 1a). [76] Tang et al reported synthesizing a carbon-coated Li 4 Ti 5 O 12 (LTO/C) composite through the direct pyrolysis of a Li-doped Ti-MOF precursor in N 2 at 800 and 900 °C, denoted as LTO/C-800 and LTO/C-900, respectively. The as-prepared products showed a remarkable rate capability and high cycling performance.…”
Section: Metal Oxide/carbonmentioning
confidence: 99%
“…The direct growth of self‐supported ternary transition metal oxides on current‐collecting substrates was recently explored to overcome the drawbacks of mixing active electrode materials with binders and conductive additives, and the anode materials showed enhanced endurance and fast discharge–charge processes; in particular, CuCo 2 O 4 (Figure ) has exhibited good Li + storage properties because both anions contribute to the faradaic redox mechanism for electrochemical energy storage . However, CuCo 2 O 4 ‐based anodes suffer from large volume change upon cycling, causing drastic capacity fading that results in a short discharge–charge cycle life.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a strategy for the fabrication of novel anode materials having specific surface areas maximized via morphology engineering, without losing other material properties, should be developed. In addition, 3D network structures of active materials can allow a large surface area for reactions and open channels for an efficient ion–electron transport, which are both important properties for their use in LIBs …”
Section: Introductionmentioning
confidence: 99%